Surgical Management of Symptomatic Olecranon Traction Spurs. Issue 7 (18th July 2014) - Alvi, Hasham M.; Kalainov, David M.; Biswas, Debdut; Soneru, Alexander P.; Cohen, Mark S.
Background: There is a paucity of information pertaining to the pathoanatomy and treatment of symptomatic olecranon traction spurs. Purpose: To describe the pathoanatomy of olecranon traction spur formation, a technique for spur resection, and a series of patients who failed conservative care and underwent operative treatment. Study Design: Case series; Level of evidence, 4. Methods: Eleven patients (12 elbows) with a mean age of 42 years (range, 27-62 years) underwent excision of a painful olecranon traction spur after failing conservative care. Charts and imaging studies were reviewed. All patients returned for evaluation and new elbow radiographs at an average of 34 months (range, 10-78 months). Outcome measures included the Quick-Disabilities of the Arm, Shoulder, and Hand (QuickDASH) questionnaire; the Mayo Elbow Performance Score (MEPS); visual analog scales (VAS) for pain and patient satisfaction; elbow motion; elbow strength; and elbow stability. Results: The traction spur was found in the superficial fibers of the distal triceps tendon in all cases. The mean QuickDASH score was 3 (range, 0-23), the mean MEPS score was 96 (range, 80-100), the mean VAS pain score was 0.8 (range, 0-3), and the mean VAS satisfaction score was 9.6 (range, 7-10). Average elbow motion measured 3° to 138° (preoperative average, 5°-139°). All patients exhibited normal elbow flexion and extension strength, and all elbows were deemed stable. Early postoperative complications involved a wound seroma in 1 case and olecranon bursitis in 1 case: both problems resolved without additional surgery. Two patients eventually developed a recurrent traction spur, 1 of whom underwent successful repeat spur excision 48 months after the index operation. Conclusion: Short- to mid-term patient and examiner-determined outcomes after olecranon traction spur resection were acceptable in our experience. Early postoperative complications and recurrent enthesophyte formation were uncommon. Clinical Relevance: This study provides the treating physician with an improved understanding of the pathoanatomy of olecranon traction spur formation, a technique for spur resection, and information to review with patients regarding the outcome of surgical management.